Implementation Intention Strategy to Reduce Salt Intake among Heart Failure Patients: A Randomized Controlled Trial - Andressa Teoli Nunciaroni; Rúbia de Freitas Agondi; Henrique Ceretta Oliveira; Rafaela Batista dos Santos Pedrosa; Roberta Cunha Matheus Rodrigues; Maria Cecília Gallani (Réseau de recherche en interventions en sciences infirmières du Québec (RRISIQ), 2021)
Introduction: An Implementation Intention strategy might be effective in transforming a positive intention to reduce salt intake into effective action among heart-failure patients. Objective: To assess the potential efficacy of an Implementation Intention intervention to reduce salt intake among heart-failure patients. Methods: Randomized controlled trial. The 60 heart-failure patients recruited were first randomized into 2 groups: an experimental group (EG) and a control group (CG). The study population was further broken down into 4 groups depending on whether the individuals prepared their own meals: 2 individual groups (EG-Individual and CG-Individual); and 2 collaborative groups, involving the patient and a social referent (EG-Collaborative and CG- Collaborative). The experimental groups developed action and coping plans based on the Implementation Intention. Total salt intake was calculated through discretionary salt, sodium-food frequency questionnaires, and 24-hour recall, obtained at the baseline (T0) and at the 2-month follow-up (T3). Results: 56 patients ended the follow-up. A reduction in the total salt intake was observed in the EGs (Individual and Collaborative) compared to baseline (5.04g/day vs. 12.21g/day for the EG-Individual (p≤0.001); 4.79g/day vs. 11.43g/day for the EG-Collaborative; p≤0.001). The multivariate analysis showed that the 2 EGs had lower salt intake at T3 than the 2 CGs (95% CI 4.19-9.29 for individual groups vs. 95% CI 4.84-10.22 for collaborative groups). There were no differences between the 2 EGs (95% CI -2.77 to 2.41). The total variance explained (R2) by these comparisons was 0.70. Discussion and conclusion: This study suggests that Implementation Intention might be effective in reducing salt intake among heart-failure patients, either individually or collaboratively. Further research testing mediator and moderator effects of the psychosocial variables are recommended.